Piano Performance In Varta And Its PedagogicalSignificance In The Modern Music EducationSystem - Baratova Yulduz Ahmadovna (Euro Asian Journal Publishing, 2025)
This scientific article is devoted to highlighting the theoretical, performing and pedagogical foundations of pop piano performance. Pop piano is one of the important directions of modern musical art, which combines the traditions of classical piano with the performing styles of jazz, pop, rock and popular music. The article scientifically analyzes the process of formation, stylistic features, technical and artistic aspects of pop piano performance, as well as the issues of teaching it in the music education system.
Keywords: pop piano; pop performance; contemporary music